Digitalization of Cultural Heritage and Local Product Marketing: Mapping Research Trends and Future Directions - Astri Ayu Purwati; Muhammad Luthfi Hamzah (INVEST : Jurnal Inovasi Bisnis dan Akuntansi, 2025)
The rapid expansion of digital technologies has transformed how cultural heritage is preserved, represented, and commercialized in contemporary markets. This study aims to systematically map research trends concerning the digitalization of cultural heritage and its implications for local product marketing during the 2020–2025 period. Using a Systematic Literature Review (SLR) approach guided by the PRISMA framework, 25 Scopus-indexed journal articles were analyzed to identify dominant themes, methodological patterns, and emerging research directions. The findings reveal four major thematic clusters: digital transformation and cultural governance, digital marketing and MSME competitiveness, cultural identity and consumer psychology, and technological innovation through artificial intelligence and immersive media. The results indicate that digitalization enhances market reach and engagement for culturally embedded local products; however, sustainable competitiveness depends not only on technological adoption but also on authenticity, narrative coherence, and institutional readiness. Emerging trends show increasing integration of AI and immersive technologies, stronger alignment with sustainability discourse, and growing cross-national comparative studies, while longitudinal and multi-level governance research remains underdeveloped. This study contributes by integrating fragmented research streams into a multidimensional analytical framework that connects cultural preservation with digital market performance. The findings provide theoretical advancement and practical insights for policymakers, cultural institutions, and local enterprises seeking to balance technological innovation with cultural integrity in digital marketplaces.